Pengaruh Penambahan Enzim Fitase Pada Ransum terhadap Berat Relatif Organ Pencernaan Ayam Broiler - Meisji Liana Sari; F. Gurki N Ginting (Agricultural Faculty, 2012)
The effect of supplementation phytase enzyme into poultry feed on the relative weight of broiler's digestive organs ABSTRACT. The objective of this research was to know the effect of enzim phytase supplementation on relative organ digestion broiler. The research was done for weeks at Animal Fees and Nutrition, Faculty of Agriculture, Sriwijaya University in Mei to Juni 2008 utilized. A Completely Randomized Design with 6 treatments P0 (100% basal diet), P1 (100% basal diet + 500 FTU/kg), P2 (100% basal diet + 600 FTU/kg), P3 (100% basal diet + 700 FTU/kg), P4 (100% basal diet + 800 FTU/kg),P5 (100% basal diet + 900 FTU/kg). Each treatments was replicated for 3 times. The parameters are final body weight, (%) proventrikulus, (%) relatif intestine, (%) pancreas and (%) liver weigh broiler chickens . The research showed that adding enzim phytase has join no significant effect (P0.05) on the body, liver, proventrikulus, ventrikulus weight, bur it showed significant effect on relative intestines and pancreas weight (P0.05) of broiler chickens . the average weight of body weight was 1117.50-1873.00 gram, proventrikulus was 0,44-0,64% ventrikulus was 1.30-2.32%, intestine was 2.74-4.39%, pancreas was 0,21-0,32% and liver was 2,35-3.01%.